Agency-Theorie, Informationskosten und Managervergütung - Ulrike Graßhoff; Joachim Schwalbach (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
Agency theory assumes a potential conflict of interest between principal and agent. Principals provide incentives to agents to influence agents' behaviour in the interest of the principal. In practice, incentive systems are dominanted by financial incentives and consist of fixed and performance related variable pay. Empirical studies concentrated on the analysis of the sensitivity of variable pay. Most studies found very low values which were considered too low to have any incentive effect. This paper tries to give a theoretical answer to the empirical puzzle of low incentive factors. In the first step, we show that low values of the incentive factor occur if high environmental uncertainty, high risk aversion by the agent and/or high opportunity costs for the agent exist, In the second step, we show that investments in information gathering by the principal to reduce uncertainty lead to higher incentive factors as well as higher returns for the principal. The magnitude of improved returns is shown by assuming various information cost functions.
urn:nbn:de:kobv:11-10056099
Keywords: 330